Use of cover crops for sustainable soil management associated with corn (Zea mays L.) cultivation (Scientia Agropecuaria, 2021)
Soil is a living, dynamic entity and at the same time vulnerable to degradation, if it is not managed with sustainable practices, causing low crop yields. The objective of this research was to determine the effects of plant cover associated with the cultivation of corn on soil properties: bulk density, gravimetric moisture, soil pH and electrical conductivity, organic matter, estimation of nitrogen supply when leaf biomass is incorporated, and finally corn yield. The study was conducted under a randomized complete block experimental design with five treatments: corn without cover crop (control), corn with clover cover crop; corn with vetch cover crop; corn with vetch + oats cover crop and corn with dead cover crop (mulch). The results showed that corn associated with clover, vetch and mulch (dead cover) increased grain yield (kg.ha-1) of corn by 44%, 37% and 38%, respectively, compared to planting corn without any type of cover. Likewise, the use of clover, vetch and vetch cover crops associated with oats increased soil organic matter and soil input by 253, 163 and 149 kg ha-1 of nitrogen if the leaf biomass of the cover crops was incorporated into the soil. Therefore, the corn-clover association is the one that presents the best results to increase yields under sustainable soil management and agroecological principles.
Keywords: vegetative cover; soil management; Trifolium spp; sustainability